Magnetic resonance imaging shows spinal curvature in Chinook salmon (Oncorhynchus tshawytscha) is associated with chronic inflammation of peri-vertebral soft tissues. - Lovett BA; Firth EC; Perrott MR; Munday JS; Pontre BP; Lydon A-MP; Symonds JE; Preece MA; Herbert NA (John Wiley and Sons, Inc., 2024)
Chinook salmon (Oncorhynchus tshawytscha) farmed in New Zealand are known to develop abnormal spinal curvature late in seawater production. Its cause is presently unknown, but there is evidence to suggest a neuromuscular pathology. Using magnetic resonance imaging (MRI), we evaluated the relationship between soft tissue pathology and spinal curvature in farmed Chinook salmon. Regions of interest (ROIs) presenting as pathologic MRI signal hyper-intensity were identified from scans of 24 harvest-sized individuals: 13 with radiographically-detectable spinal curvature and 11 without. ROIs were excised from individuals using anatomical landmarks as reference points and histologically analysed. Pathologic MRI signal was observed more frequently in individuals with radiographic curvature (92%, n = 12) than those without (18%, n = 2), was localized to the peri-vertebral connective tissues and musculature, and presented as three forms: inflammation, fibrosis, or both. These pathologies are consistent with a chronic inflammatory process, such as that observed during recovery from a soft tissue injury, and suggest spinal curvature in farmed Chinook salmon may be associated with damage to and/or compromised integrity of the peri-vertebral soft tissues. Future research to ascertain the contributing factors is required.
Keywords: Chinook salmon; MRI; chronic inflammation; finfish skeletal health; neuromuscular pathology; spinal curvature; Humans; Animals; Salmon; Fish Diseases; Spine; Spinal Curvatures; Inflammation